Aggression Levels Affect Social Interaction in the Non‐Breeding Territorial Aggression of the Weakly Electric Fish, Gymnotus omarorum. (6th September 2014) - Zubizarreta, Lucía; Stoddard, Philip K.; Silva, Ana; Koenig, W.
Abstract Animals typically decide whether to fight or retreat from conspecifics based on their individual estimates of the costs and benefits of fighting. Theoretical models predict how contenders solve a conflict, but the evaluation processes involved in these decisions depend on multiple factors that are difficult to explore experimentally. We addressed these questions using the non‐breeding territorial aggression of Gymnotus omarorum, in which subordinates make three distinctive decisions to signal their submission during a fight: (1) interruption of their electric discharges to hide from the dominant, (2) stop attacking and retreat, and (3) emission of 'chirps', transient submissive electric signals. We confirmed that subordinates take into account the aggressive performance of dominants to shape their own agonistic decisions and performance. The intensity of aggression is highly correlated with an agonistic dyad, and the decision of subordinates to retreat is influenced by the attack rates of dominants. When we lowered the aggression of expected dominants with a 5‐HT1A receptor agonist, the correlation between the two contenders' aggression levels was lost and subordinates completely stopped emitting electric chirp signals. The aforementioned results contribute to the understanding of the decision‐making strategies driven by social challenge inherent to agonistic encounters.